Synaptotagmin 1 oligomers clamp and regulate different modes of neurotransmitter release - Tagliatti, Erica (2020)
Synaptotagmin 1 (Syt1) synchronizes neurotransmitter release to action potentials (APs) acting as the fast Ca2+ release sensor and as the inhibitor (clamp) of spontaneous and delayed asynchronous release. While the Syt1 Ca2+ activation mechanism has been well-characterized, how Syt1 clamps transmitter release remains enigmatic. Here we show that C2B domain-dependent oligomerization provides the molecular basis for the Syt1 clamping function. This follows from the investigation of a designed mutation (F349A), which selectively destabilizes Syt1 oligomerization. Using a combination of fluorescence imaging and electrophysiology in neocortical synapses, we show that Syt1F349A is more efficient than wild-type Syt1 (Syt1WT) in triggering synchronous transmitter release but fails to clamp spontaneous and synaptotagmin 7 (Syt7)-mediated asynchronous release components both in rescue (Syt1−/− knockout background) and dominant-interference (Syt1+/+ background) conditions. Thus, we conclude that Ca2+-sensitive Syt1 oligomers, acting as an exocytosis clamp, are critical for maintaining the balance among the different modes of neurotransmitter release.